The investigation of the deformations of the elastic bodies with thin coating using D-adaptive finite element model - Kossak, О.; Savula, Y. (Фізико-математичне моделювання та інформаційні технології, 2010)
A D-adaptive mathematical model that combines elastic structures with a thin coating is analysed. The main idea of this approach is based on the formulation of the combined model, which allows the use of 3-D elasticity theory model over one part of the domain, and 2-D Timoshenko’s shell model over the other part. The boundary and variation formulation of the D-adaptive model problem are presented. The numerical results are compared with available exact solutions. The numerical results demonstrate the applicability of this approach. У статті наведено аналіз D-адаптивної математичної моделі, яка поєднує пружні конструкції з тонким покриттям. Цей підхід базується на формулюванні комбінованої математичної моделі, яка дозволяє використовувати одночасно тривимірну лінійну модель теорії пружності в області масивних фрагментів конструкції та двовимірну модель теорії оболонок типу Тимошенка в області покриття. Записано граничне та варіаційне формулювання задачі. Для окремих випадків проведено порівняння отриманого числового розв’язку з аналітичним. В статье анализируется D-адаптивная математическая модель, которая объединяет упругие конструкции с тонким покрытием. Этот подход базируется на формулировании комбинированной математической модели, которая использует одновременно трехмерную линейную модель теории упругости в области массивных фрагментов конструкции и двухмерную модель теории оболочек типа Тимошенко в области покрытия. Записана граничная и вариационная постановка задачи. Для отдельных случаев проведено сравнение полученного численного решения с аналитическим.